2018
DOI: 10.1038/s41598-018-33042-5
|View full text |Cite
|
Sign up to set email alerts
|

Robust Enhancement of Lentivirus Production by Promoter Activation

Abstract: Lentiviral vectors are a valuable tool to deliver exogenous genes for stable expression in cells. While much progress has been made in processing lentiviral vector-containing culture medium, it remains to be explored how the production of lentiviral vector from producer cells can be increased. We initially found that co-expression of the SPRY domain-containing SOCS box protein 1 (SPSB1) promotes the production of human immunodeficiency virus type 1 (HIV-1) and lentiviral vector with increased expression of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…In the flow-through, no signal was detected showing that the Lenti VSVG Affinity Matrix could successfully capture the VSVG-LVs particles without resin saturation. In contrast, a strong signal was found in the elution fraction, which exhibited the characteristic LVs p24 pattern [ 61 , 62 ], supporting that an efficient viral elution occurred. For the strip sample, a subtle signal was detected, although it was stronger for the p24 protein.…”
Section: Resultsmentioning
confidence: 99%
“…In the flow-through, no signal was detected showing that the Lenti VSVG Affinity Matrix could successfully capture the VSVG-LVs particles without resin saturation. In contrast, a strong signal was found in the elution fraction, which exhibited the characteristic LVs p24 pattern [ 61 , 62 ], supporting that an efficient viral elution occurred. For the strip sample, a subtle signal was detected, although it was stronger for the p24 protein.…”
Section: Resultsmentioning
confidence: 99%
“…Article https://doi.org/10.1038/s41551-023-01013-5 enhancer, and showed that we could increase viral titres in the presence of Tax 65 , and to a greater extent when combined with NovB2.…”
Section: Nature Biomedical Engineeringmentioning
confidence: 85%
“…By use of c92 cells in perfusion mode bioreactors (and with multiple harvesting), 8 £ 10 10 transduction units can be generated per liter. In an alternate approach, ectopic expression of HTLV-1 −derived tax, an enhancer for several common transcription factors (e.g.., AP1, ATF, NFKB) [28], has recently been reported to boost lentivirus production in 293-T cells up to 10-fold [29]. For lentiviruses prepared using these progressive systems, the present findings underscore the importance of critically assessing possible cytotoxic activity for such large-scale virus preparations; the load of possibly damaged and inactive virus; and the effectiveness of these viruses in efficiently transducing refractive primary cell populations.…”
Section: Discussionmentioning
confidence: 99%